RANCANG BANGUN MEDIA PEMBELAJARAN “PERKEMBANGBIAKAN PADA HEWAN’MENGGUNAKAN TEKNIK MOTION GRAPHIC ( Studi Kasus MTs Muhammadiyah Kasihan ) - Agus Purwanto; Ibnu Hadi Purwanto; Muhammad Arbi Hamam (Jurnal Informatika Teknologi dan Sains (Jinteks), 2023)
MTs Muhammadiyah pity is one of the private educational institutions located in the Bangunjiwo area, Kasihan, Bantul. At MTs Muhamadiyah Kasihan there is a Natural Science lesson in which there is material for breeding in animals. Some students at MTs Muhammadiyah are sorry that it is still difficult to imagine how the process of breeding these animals. Just looking at pictures is still not enough to explain the process of reproduction in animals. Motion graphic technique is a technique in the development of animation from graphic design that can turn images or photos into videos. It is hoped that the motion graphic video for learning animal reproduction in this study can clarify students' understanding of the material and assist teachers in explaining the material to their students. The process of testing this learning video uses a questionnaire addressed to media and material experts, and to users, namely class IX students at MTs Muhammadiyah Kasihan. Based on the results of the questionnaire, the results of calculations with a Likert scale showed that 88.95% were included in the "very good" category.